UJI BEBERAPA VARIETAS DAN PEMBERIAN PUPUK BIOBOST TERHADAP PERTUMBUHAN DAN PRODUKSI BAWANG MERAH (Allium ascolonicum L.) - Lubis, Rafiqah Amanda (BIOLINK (Jurnal Biologi Lingkungan, Industri, Kesehatan), 2017)
This research aims was to know Test of Some Varieties and Provision of Bioboost Fertilizer on the Growth and Production of Red Onion (Allium ascolonicum L.). The design used in this research is Randomized Block Design, with 2 factors is: Factor Test Some varieties symbolized with (V) consists of 3 levels: V1 = Local Variety, V2 = Varieties of Brebes, V3 = Philippine Varieties. The Bioboost Fertilization Factor is symbolized by (B), is: B0 = 0 cc / Liter water, B1 = 3.5 cc / Liter water, B2 = 5cc / Liter water, B3 = 10 cc / Liter water. The result of analysis of variance that effect of some varieties treatment showed real effect at plant height 7 mst. While the influence is not real in the observation on the observation of plant height aged 3.5 and 9 mst. Number of tillers 3, 5, 7 and 9 mst. Tuber weight per sample and weight of tuber per plot.Â  Treatment of Bioboost fertilizer showed real effect on observationÂ  weight of tuber per plot. While the effect was not significant on the observation of plant height aged 3, 5, 7 and 9 mst, the number of tillers aged 3, 5, 7 and 9 mst and tuber weight per sample. analysis of variance that due to the treatment of several varieties and fertilizer Bioboost showed a real effect on observation of height of plant age 7 and 9 mst. While the effect was not significant on observation of height parameters of plant age 3 and 5 mst, number of tillers age 3, 5, 7 and 9 mst, tuber weight per sample and weight of tuber per plot.